Benthic foraminifera across the Albian–Cenomanian transition and their paleoceanographic significance during OAE1d in the western Tethys (Umbria–Marche Basin, Italy) - Giraldo-Gomez V. M.; Petrizzo M. R.; Gambacorta G.; Bottini C.; Gilardoni S. E.; Erba E. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)
The benthic foraminiferal assemblages from the upper Albian-lower Cenomanian interval of the Scaglia Bianca Formation in the Monte Petrano (MP) and Le Brecce (LB) sections (Umbria–Marche Basin; Italy) provide a detailed record of the faunal changes across the Oceanic Anoxic Event 1d (OAE 1d). Fluctuations in abundance, diversity, and species composition reflect variations in bottom-water oxygenation and organic carbon fluxes. Benthic foraminifera are integrated with planktonic foraminifera, calcareous nannofossils, and geochemical proxies to reconstruct the bottom and surface water conditions across the OAE 1d in the Umbria–Marche Basin. The pre-OAE 1d interval was characterized by benthic foraminifera that thrived under stable mesotrophic condition in bottom waters. In surface waters, planktonic foraminifera indicate dominant mesotrophic conditions in agreement with calcareous nannofossil assemblages suggesting a regime of higher fertility under cooler conditions. During the OAE 1d interval, benthic foraminifera display an increase in the abundance of infaunal taxa, suggesting mesotrophic conditions in bottom waters. Nevertheless, within the Pialli Level, the six laminated black-to-dark grey shale horizons (MP1/LB1 to MP6/LB6), benthic foraminifera are absent or highly impov- erished (MP1, MP2, MP4, MP6, LB5, LB6), suggesting hypoxic/anoxic conditions in bottom waters. Planktonic foraminifera in this interval reflect mesotrophic to oligotrophic conditions under the presence of an expanded mixed layer and deeper thermocline in the surface waters. Calcareous nannofossils record warm conditions and lower fertility starting just prior to and across the OAE 1d. However, higher values of fertility are recorded in the black-to-dark grey shales MP3/LB3, MP4/LB4 and MP5/LB5 of the Pialli Level. The post-OAE 1d interval is marked by an increase in the diversity of benthic foraminifera, indicating a restoration of the oxygen conditions in a continuous mesotrophic regime in bottom waters. The surface waters experienced ...